PENERAPAN METODE AL MIFTAH LIL-ULUM DALAM MENINGKATKAN KEMAMPUAN MEMBACA KITAB KUNING FATHUL QORIB PONDOK PESANTREN AL- HAYYAT KALIMANTAN UTARA - Iqbal Musthofa Fihri; Iva Inayatul Ilahiyah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to describe the implementation of the Al-Miftah Lil Ulum method in improving the ability to read classical Islamic texts (kitab kuning), specifically Fathul Qorib, at Pondok Pesantren Al-Hayyat, North Kalimantan. The research employs a qualitative approach with a descriptive method. Data were collected through observation, interviews, and documentation. The findings reveal that the Al-Miftah Lil Ulum method—focusing on mastery of Arabic grammar (nahwu and shorof) as the foundation for understanding Arabic texts—is systematically applied by instructors during kitab kuning learning sessions. The application of this method significantly enhances students’ comprehension of sentence structures, vocabulary meanings, and legal contexts in Fathul Qorib. Supporting factors include teacher consistency, a gradual learning approach, and practical translation exercises (both manthuq and mafhum). In conclusion, the Al-Miftah Lil Ulum method proves effective in improving students’ reading and understanding of classical Islamic texts.